Environmental contamination in the Keban mining district, eastern Turkey - Boeluecek, Cemal (Springer Heidelberg, 2007)
The present research is focused on the contribution of base-metal mining to heavy-metal contamination of the environment. Mining wastes and unworked ore-mineral concentrations present in the Keban region (eastern Turkey) are the main sources of environmental contamination in the area via leaching of potentially toxic elements. Total-element concentrations of several different sampling media, such as sediments, waters, and plants, were measured. Analyses of metal and metalloid concentrations of sediment samples indicate high As, F, Mo, and Zn contents, which decrease exponentially with distance from the mine and mineralized zones, mainly due to dilution by water and barren material. The average concentrations of As, Cd, Cr, Pb, and Ta in the water samples are higher than the average natural background values for these heavy metals. The most significant components of the water samples under study are (>1 mg/l) Ca, Cl, K, Mg, Mn, Na, Zn, and S, and (<1 mg/l) Ba, Fe, and Mo; these samples are also enriched in some toxic elements, such as As, Cd, Cr, Pb, and Sb. Red algae have a higher capacity for absorption of Cr, Cu, Mn, Ni, Pb, and S, whereas green algae are enriched in Co, Hg, La, Se, and V. However, the highest heavy-metal and toxic-element contents are found in moss collected at the mine adit.
Keywords: Keban; environmental contamination; algae; moss; stream sediment